MENINGKATKAN KUALITAS KEHIDUPAN BERBANGSA MELALUI BUDAYA DEMOKRASI - Wilujeng, Sri Rahayu (Faculty of Humanities, Diponegoro University, 2014)
Abstract Democracy is the old issue has been discussed for long time anthusiasly. This idea of democracy appeared in Greek about two thousand and five hundred years ago. Now day implementation of democracy keep going on developed to get the best performance. The Indonesian Constitution stated. Democracy as a system in running government. Thus, consequently of this choice it must be applied imperatively. In fact, there are many problems appeared caused by implementation of democracy. It may not be comprehended as a political system. Basically this system arranges so many interests in society such as state and citizens. Thus such a system must be help by a supporting culture. That is democratic culture. This writing tries to descript what kind a culture have to develop in Indonesia. This culture is bear on a mental and moral attitude. It bases on Pancasila as a philosophy of Indonesia.Â It doesnâ€™t only caused democracy running well, but it also guards democracy donâ€™t losing its essence. Finally, democracy gives advantages for people as the owner of sovereignty. Keywords: democracy, culture, Pancasila